2020
DOI: 10.3390/ijms21145067
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Ouabain Modulates Expression of Claudins in Rat Intestine and Cerebral Blood Vessels

Abstract: The ability of exogenous low ouabain concentrations to affect claudin expression and therefore epithelial barrier properties was demonstrated previously in cultured cell studies. We hypothesized that chronic elevation of circulating ouabain in vivo can affect the expression of claudins and tight junction permeability in different tissues. We tested this hypothesis in rats intraperitoneally injected with ouabain (1 μg/kg) for 4 days. Rat jejunum, colon and brain frontal lobes, which are variable in the expresse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 68 publications
(123 reference statements)
0
15
0
Order By: Relevance
“…However, with a lack of claudin-2 expression, the TJ expression pattern of IPEC-J2 appears to be very close to Peyer's patches follicle-associated epithelium, therefore representing the main relevant epithelium involved in immune surveillance in the intestine [51,52]. Currently, many studies demonstrate the susceptibility and reliability of the non-malignant porcine epithelial cell line IPEC-J2 regarding a wide variety of mechanisms in native tissue of different species in vitro [19,53].…”
Section: Discussionmentioning
confidence: 99%
“…However, with a lack of claudin-2 expression, the TJ expression pattern of IPEC-J2 appears to be very close to Peyer's patches follicle-associated epithelium, therefore representing the main relevant epithelium involved in immune surveillance in the intestine [51,52]. Currently, many studies demonstrate the susceptibility and reliability of the non-malignant porcine epithelial cell line IPEC-J2 regarding a wide variety of mechanisms in native tissue of different species in vitro [19,53].…”
Section: Discussionmentioning
confidence: 99%
“…As I sc reflects the intensity of ion transport through the epithelium, I sc decrease and change in sign from positive to negative probably indicates a dramatic change in the vector of ion transport between the intestinal lumen and the internal environment observed by 72 h after 10 Gy irradiation. Na,K-ATPase is known to establish a transmembrane gradient of sodium and potassium ions (Matchkov & Krivoi, 2016) and functionally interact with claudins (Markov et al, 2020). Earlier in proteomic studies, it was shown that the expression of the Atp1b3 gene, encoding one of the subunits of Na,K-ATPase, is significantly modulated in ileum epithelium of mice when exposed to ionizing radiation (Huang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that radiation disrupts intestinal epithelial tight and adherens junctions, as well as actin cytoskeleton (Shukla at al., 2016). Na,K-ATPase, which plays a critical role in polarity and vectorial transport across epithelial cells and functionally interacts with claudins (Markov et al, 2020), is also a radiation target (Huang et al, 2019). The ability of circulating ouabain, a specific ligand of the Na,K-ATPase, to affect claudins expression and therefore epithelial barrier properties, is also most pronounced in the jejunum (Markov et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TJ protein levels were analyzed in the colon segments, as described in detail earlier [ 70 ], and stain-free immunoblotting was performed, as described previously [ 71 , 72 , 73 ].…”
Section: Experimental Designmentioning
confidence: 99%